Luxembourg : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This paper evaluates the stability of the financial system of Luxembourg. Financial soundness indicators for Luxembourg's financial system, which plays a key role in the intermediation of financial capital, have remained relatively robust in recent years. Following rising asset prices and inflows, the investment fund industry has enjoyed strong growth in assets under management, while exposure to liquid assets has remained steady. An assessment of the financial system's ability to withstand severe but plausible shocks suggests a good deal of resilience, albeit with some risks. Insurance stress test results indicate that strong initial levels of capital and low guaranteed product exposure offer insulation against market shocks.